"A Pro-Fascist English Lady": The International Thought of Muriel Innes Currey. Issue 1 (29th March 2023) - Allen, Kye J
Abstract: This article recovers the activities, international thought, and reception of Muriel Innes Currey during the formative decades of the twentieth century. As both an ardent campaigner on behalf of the League of Nations Union and a fascist sympathizer, the paper highlights the variegated beliefs and tensions encapsulated within Currey's thinking as she attempted to reconcile advocacy for the League of Nations with a peculiar mélange of High Tory conservatism, Italophilic solidarity, and fascist sympathies. The contribution of this study is two-fold. First, building on efforts to excavate the history of women's international thought from undue obscurity, this article expands the referent of analysis to the thought and activity of a hitherto neglected woman, yet one overwhelmingly pro-fascist in orientation. Second, discerning Currey's thought contributes to redressing a double erasure within the history of the discipline: the gendered elision of women's international thinking and the concurrent amnesia surrounding fascism and its place within the then-fledgling discipline of international relations. Currey may have been on the periphery of academia; however, she was nevertheless a thinker who engaged with key questions occupying, and institutions affiliated with, the emergent field.